Belief in living a meaningful life and adjustment to chronic pain - Reed, D. E.; Day, M. A.; Ferreira-Valente, A.; Jensen, M. (Pain Medicine, 2025)
Objective: Chronic pain is a global health concern and often interferes with multiple aspects of individuals’ lives (eg, physical activities), diminishing a person’s ability to engage in activities that promote meaning in life. However, it is not well understood how believing that one can live a meaningful life despite pain could contribute to improved function among individuals with chronic pain. The aim of the present study was to better understand the role that belief in living a meaningful life despite pain might have on adjustment to chronic pain. Methods: Participants (n = 164) were individuals with chronic pain who completed baseline data from 2 closely related randomized clinical trials. Hierarchical regression analyses were used to examine the hypotheses that one’s belief in living a meaningful life despite pain will be associated with function (pain interference and symptoms of posttraumatic stress disorder, depression, and anxiety) and that the belief in living a meaningful life despite pain would moderate the associations between pain intensity and function. Results: Belief in living a meaningful life despite pain was significantly associated with less pain interference and less severe symptoms of posttraumatic stress disorder, anxiety, and depression, supporting the potential role of this variable in adaptive adjustment to chronic pain. However, one’s belief in living a meaningful life despite pain did not moderate the associations between pain intensity and function. Conclusions: Results provide important theoretical and clinical information about how believing that one can live a meaningful life despite pain might serve as an important process for adjustment to chronic pain.